The role of Facebook in the process of acquiring information. Own research study - Popiołek, Malwina (Journal of Education Culture and Society, 2020)
This paper focuses on the social network sites (SNSs), especially on Facebook, and their role in people’s daily life. It focuses on people who are statistically not at risk of the digital exclusion (young and still educating). Here are presented conclusions of the author’s own research focusing on the role of Facebook in daily life of a group of its users. Research was done as an experiment. The purpose of the study was to find out if students, who use Facebook, could stop to do it temporarily. Facebook is here regarded as a main source of various kinds of information, both private and public. In this article the author tries to prove that Facebook is one of the primary channels of information flow.